History And Autocratic Power: Vasily Zhukovsky As A Mentor Of The Tsesarevich Alexander - Raisa V. ZAMILOVA; Dmitry E. MARTYNOV; Yulia A. MARTYNOVA (Astra Salvensis, 2019)
The article is devoted to consideration of pedagogical program developed by Vasily Zhukovsky for the education of the heir to the throne – the future Emperor Alexander II. Pedagogical views of Zhukovsky are inseparable from his political preferences and philosophical-historical ideas. Pedagogical system of Zhukovsky in general terms is based on the concept of I. Pestalozzi, but it was adopted to the individual elitist education. The main task of Vasily Zhukovsky was the education of a monarch who would be able to set himself practical challenges and successfully resolve them, while based on Christian morality. The military component of the training should be reduced to a minimum. The most important means of education were history, and the personal views of Zhukovsky, transmitted to the crown Prince, were based on historical concepts developed by Karamzin and Johann von Muller. Archival materials indicate that to a large extent the teacher has achieved its objectives. In the historical views of Muller Zhukovskiy mostly singled out the idea of history as a means of moral education and the rule of law, combined with an enlightened autocratic rule. Such projects were actually doing him a "loyal opposition" and led to the resignation from the court service.